Solve for \( u \) \[ 2(u+7)=-6 u-34 \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To solve for \( u \) in the equation \( 2(u+7)=-6u-34 \), let's start by distributing on the left side: \[ 2u + 14 = -6u - 34 \] Next, we'll add \( 6u \) to both sides to get all terms involving \( u \) on one side: \[ 2u + 6u + 14 = -34 \] This simplifies to: \[ 8u + 14 = -34 \] Now, we will subtract 14 from both sides: \[ 8u = -34 - 14 \] \[ 8u = -48 \] Finally, divide both sides by 8 to solve for \( u \): \[ u = \frac{-48}{8} = -6 \] So, the solution is: \[ u = -6 \]